Pharmacodynamic Hybrids Coupling Established Cardiovascular Mechanisms of Action with Additional Nitric Oxide Releasing Properties - Martelli, Alma; Breschi, Maria C.; Calderone, Vincenzo (Current Pharmaceutical Design, 2009)
The pharmacotherapy of complex pathological states at the cardiovascular level often requires different and complementary pharmacodynamic properties. This is frequently achieved through the administration of “cocktails”, composed by several drugs possessing different mechanisms of action. In the last years, a revision of the “one-compound-onetarget” paradigm led to a wide development of new classes of molecules, possessing more pharmacological targets. Among them, this innovative strategy produced interesting hybrid drugs, with a dual mechanism of action: a) a fundamental and well-established pharmacodynamic profile and b) the release of nitric oxide (NO), playing a pivotal role in the modulation of the function of cardiovascular system, where it induces vasorelaxing and antiplatelet responses. These new pharmacodynamic hybrids present the advantage of adding to a main mechanism of action (for example, cyclooxygenase inhibition, beta-antagonism or ACE-inhibition) also a slow release of NO, useful either to reduce the adverse side effects and/or to improve the effectiveness of the drug. This review presents the chemical features of many examples of NO-releasing hybrids of cardiovascular drugs and explains the pharmacological improvements conferred by the addition of such NO-donor properties.
Keywords: cardiovascular drugs